Effects of Coping Strategies used by University Students in the Management of their Psychosocial Problems in the University of Buea and University of Bamenda - Mboh, Bisong Prisca; Martina, Dr. Njungwa Zinkeng (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
Students' psychosocial problems are managed in and out of the school milieu, as a result students have been making use of some coping strategies for the management of these problems. one of these coping strategies is the use counselling services, peer support, extracurricular activities and spiritual services. The purpose of this study was to investigate the effects of coping strategies used by university students in the management of their psychosocial problems in the University of Buea and University of Bamenda. One specific objectives of this study was to assess the effects of guidance counselling services in the management of psychosocial problems amongst university students in the University of Buea and University and Bamenda. These research objectives were translated into research questions and research hypotheses. The study employed the mixed methods approach notably the sequential-explanatory design. In this perspective, instruments such as structured questionnaire and interview guides were used. A total of 488 students were validated for the final data analysis and 2 guidance counsellors, 2 student pastors and 2 student representive. Data from the questionnaires were digitalized with the support of EpiData 3.1 and descriptive and inferential statistical analyses were done with the support of SPSS version 26.0. As for the qualitative data, their abstraction was reduced through the systematic process of thematic analysis. The findings for this study show that, amongst the four indicators of the independent variable operationalized in this study, guidance counseling services (r-comp=0.703) are the most effective in managing psychosocial problems This therefore implies that the conceptual components significantly has an impact on university students’ capacity to manage their psychosocial problems. It was recommended that, the training of school guidance counselors while in their professional schools should be given more attention, as they are very effective in the management of students’ psychosocial problems.